DEVELOPMENT OF WORD WALL MEDIA TO TEACH VOCABULARY FOR EIGTH GRADE STUDENTS OF MTs SIROJUT THOLIBIIN SUTOJAYAN - Anita Lestari; Siti Rofi'ah; Istina Atul Makrifah (PROJECT (Professional Journal of English Education), 2023)
This study aims to develop word wall media as a vocabulary learning media for eighth garde students of MTs Sirojut Tholibiin Sutojayan in recount text material. That focuses on word meaning, pronounce words and classifiying word types (adjectives, noun, adverb, and verb). Besed on the result of interviews with English teacher, students are still lacking in vocabulary mastery, very few students carry English dictionaries. According to observation the result of with their students they only used textbooks without using other media. The reseracher conduct Research and Development which was developed by Dick and Carry (1996), namely ADDIE there are five steps, namely (analyze, design, development, implementation and evaluation). The instrument in this study used field notes, interview guides, and questionnaires. The techniques used are questionnaires, observation, interview and documentation. The result of research show that learning by using word wall media is powerful for teaching vocabulary to eighth grade students of MTs Sirojut Tholibiin Sutojayan. Students become easy to remember the meaning of the newly known vocabulary and students understand the types of word classification. Keywords:  ADDIE Method; Teaching Vocabulary; Word Wall Media